2005
DOI: 10.1111/j.1741-2358.2005.00087.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dry mouth conditions on oral health‐related quality of life in older people

Abstract: Dry mouth (objective and subjective) is significantly associated with oral health-related quality of life strengthening the value of monitoring dry mouth conditions in the care of frail old people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
131
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 149 publications
(152 citation statements)
references
References 34 publications
10
131
1
5
Order By: Relevance
“…This datum may point that both BMS and dry mouth seem to affect mainly the population aged 50 years or around (1,15,24) . Regarding patients' clinical history, the symptomatic groups showed similarities in may aspects, which agrees with the reviewed literature (2,(4)(5)(6)(7)(8)11,16,22,23) . Some studies, however, found variations especially regarding the intensity of the symptom (4,22,24) .…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…This datum may point that both BMS and dry mouth seem to affect mainly the population aged 50 years or around (1,15,24) . Regarding patients' clinical history, the symptomatic groups showed similarities in may aspects, which agrees with the reviewed literature (2,(4)(5)(6)(7)(8)11,16,22,23) . Some studies, however, found variations especially regarding the intensity of the symptom (4,22,24) .…”
Section: Discussionsupporting
confidence: 77%
“…Xerostomia is the main manifestation of this syndrome (19) . Dry mouth can affect the oral mucosa as a whole (20) , but subjects also state that structures such as the lips (21) and the oropharynx (16,22) are also affected. The symptom can occur continuously (23) , with periods of considerable discomfort (20) .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations